1990
DOI: 10.1103/physrevb.41.12260
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-induced line broadening in first-order Raman scattering from graphite

Abstract: First-order Raman scattering from graphite irradiated by an electron beam has been studied by using the laser microprobe technique. An approximately linear relation is exhibited between the linewidth of the E, g mode and the reciprocal of the crystallite size. The observed linewidths are larger than those calculated by using the known dispersion curve and the wave-vector uncertainty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 18 publications
1
63
1
Order By: Relevance
“…These are: (i) the full width at half maximum (FWHM) of the D band, which is an indicator of the amount of disorder in the carbon support: the larger it is, the greater is the disorder, and (ii) the ratio of the area of the D band to the area of the G band: the larger is this ratio, the greater is the disorder in the carbon support. Since the graphitization or the crystallinity of the carbon support imply the notion of defect-free and order in this carbon support, the most graphitized or crystalline catalysts will be those with the smallest FWHM of the D band and also those with the smallest ratio for the area of the D band to the area of the G band [37,[49][50][51][52]. Fig.…”
Section: Raman Spectroscopy and Catalyst Stabilitymentioning
confidence: 99%
“…These are: (i) the full width at half maximum (FWHM) of the D band, which is an indicator of the amount of disorder in the carbon support: the larger it is, the greater is the disorder, and (ii) the ratio of the area of the D band to the area of the G band: the larger is this ratio, the greater is the disorder in the carbon support. Since the graphitization or the crystallinity of the carbon support imply the notion of defect-free and order in this carbon support, the most graphitized or crystalline catalysts will be those with the smallest FWHM of the D band and also those with the smallest ratio for the area of the D band to the area of the G band [37,[49][50][51][52]. Fig.…”
Section: Raman Spectroscopy and Catalyst Stabilitymentioning
confidence: 99%
“…The D-band is related to structural disorder in the graphene structures and defects on carbon black. The G-band is another important feature which can be assigned to the tangential shear mode corresponding to the crystalline and ordered graphene sheet [50,51]. The relative intensity of the D-band and G-band was calculated as a good index to confirm the degree of graphitization and evaluate the relative purity of samples as shown in Fig.…”
Section: Raman Analysismentioning
confidence: 99%
“…[37][38][39][40] Previous studies have shown that in microcrystalline graphite and disordered carbon, new peaks appear at about 1355 (D) and 1620 cm À1 (D') in addition to the E 2g mode observed for large singlecrystals. [38][39][40] These features arise in general from nonzero-center phonons and are related to peaks in the density of states. Moreover, all new first-order peaks have counterparts in the second-order Raman spectrum of graphite.…”
Section: Resultsmentioning
confidence: 99%